2015
DOI: 10.7554/elife.04876
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanisms regulating mechanical force-induced Ca2+ signals at the plasma membrane and the ER in human MSCs

Abstract: It is unclear that how subcellular organelles respond to external mechanical stimuli. Here, we investigated the molecular mechanisms by which mechanical force regulates Ca2+ signaling at endoplasmic reticulum (ER) in human mesenchymal stem cells. Without extracellular Ca2+, ER Ca2+ release is the source of intracellular Ca2+ oscillations induced by laser-tweezer-traction at the plasma membrane, providing a model to study how mechanical stimuli can be transmitted deep inside the cell body. This ER Ca2+ release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 79 publications
6
98
0
1
Order By: Relevance
“…[38] This suggests that the integrin-FAK complex might be connected with TRPM7 at DRM microdomain via cytoskeleton (CSK)-actomyosin network to regulate Ca 2+ signals. [41] Using this siRNA method, we observed that TRPM7 knockdown significantly inhibited the rigidity-dependent Ca 2+ mobilization at the DRM region, with nontargeting (NT) siRNA (control group) having minimal effects (n = 5-9, ***P < 0.001) (Figure 4e,f and Figure S6, Supporting Information). For example, TRPM7 regulates focal adhesions by controlling m-calpain, [39] and the inhibition of TRPM7 disrupts the actin cytoskeleton, and the focal assembly of myosin IIA and vinculin, a focal adhesion protein.…”
Section: Trpm7 Contributes To Ca 2+ Mobilization At Drm Regionmentioning
confidence: 93%
“…[38] This suggests that the integrin-FAK complex might be connected with TRPM7 at DRM microdomain via cytoskeleton (CSK)-actomyosin network to regulate Ca 2+ signals. [41] Using this siRNA method, we observed that TRPM7 knockdown significantly inhibited the rigidity-dependent Ca 2+ mobilization at the DRM region, with nontargeting (NT) siRNA (control group) having minimal effects (n = 5-9, ***P < 0.001) (Figure 4e,f and Figure S6, Supporting Information). For example, TRPM7 regulates focal adhesions by controlling m-calpain, [39] and the inhibition of TRPM7 disrupts the actin cytoskeleton, and the focal assembly of myosin IIA and vinculin, a focal adhesion protein.…”
Section: Trpm7 Contributes To Ca 2+ Mobilization At Drm Regionmentioning
confidence: 93%
“…Furthermore, subcellular structures influence the transmission of mechanical forces to cells. For instance, the cell cytoskeleton and its associated molecules relay this mechanical information to locations within the cell containing mechanosensitive proteins, such as the nucleus or the ER [94]. Thus, the cytoskeleton of osteocytes likely plays a critical role in flow-induced mechanosensing [95][96][97].…”
Section: Single-cell Studies To Probe Subcellular Mechanosensation Inmentioning
confidence: 99%
“…Mechanical stimulation has been found to trigger calcium release in human mesangial stem cells (28). In our study, we recorded calcium signals from the proliferating mesenchymal tissue, an environment that, during organogenesis, creates and is exposed to mechanical forces from surrounding proliferating cells.…”
Section: Discussionmentioning
confidence: 99%